Sketching drawing techniques for product designers - Eissen, Koos. (Kaki Bukit Techpark II, Singapore Page One Publishing., 2007)
A guide to design sketching for product designers also looks at the significance of sketching and drawing in design studios and analyzes the effectiveness of drawings in relation to their intended purpose.
Keywords: Drawing -- Technique; Industrial design